Multi-criteria decision making for determining landfill location in Malaka Regency, East Nusa Tenggara Province of Indonesia - Leonarda Sofiani Rame; Widiatmaka Widiatmaka; Arief Hartono; Irman Firmansyah (Journal of Degraded and Mining Lands Management, 2022)
The absence of a landfill has increased the illegal waste disposal sites in Malaka Regency, which was established between 2013 and 2021. Therefore, this study aimed to analyze suitable and available land for the development of a landfill. The methodology used consisted of 2 analysis steps, namely land suitability and land availability. Land suitability was analyzed using a multi-criteria decision-making method, which included the slope, stone type/geology, lithology, soil type, soil texture, soil depth, soil drainage, distance from settlements, and water sources. The criteria were then weighted using the Analytical Hierarchy Process (AHP) and geographic information system for overlaying. Furthermore, the results of the land suitability analysis were used to determine its availability with the aid of spatial and regional planning (RTRW), land use, and forest area maps. The results showed that the highly suitable (S1) and available terrain for the landfill in Malaka Regency covered an area of 203.37 ha or 1.73% of the regency. Also, the analysis results indicated that there was still adequate land available for the landfill.